Reciclagem de saldos: surpresa e originalidade como fatores de geração de valor para o produto e estabelecimento de uma relação significativa entre sujeito e objeto - Haas, Tanise Linck (Universidade do Vale do Rio dos Sinos, 2012)
From the perspective of brand management, is it possible to imagine the recycling of balances as something relevant not only to the concept of sustainability but also a real element of costumer value? This paper will try to understand wich kind of feeling a recycled clothe is able to create on costumers; if the history of this clothe can deliver value to costumer and finally if the costumer´s experience with this clothe can become more important and significative, contribuiting to a pleasure relationship between consumer and product/brand.
Keywords: Sistema produto; Reciclagem saldos; Design emoção; Gestão marcas; Comportamento consumo; Saldo varejo; Sustentabilidade; Descarte; Valor